Enhancing Vocational Students’ Socio-Emotional Adjustment through Artificial Intelligence Supported Learning - Sari Indrayani; Rita Nur Anjani (AI and Developmental Insights in Education, 2026)
Artificial intelligence (AI) is increasingly embedded in school learning environments, yet evidence remains limited on its developmental value in vocational secondary education. This quasi-experimental study examined whether an eight-week AI-supported socio-emotional learning and AI literacy intervention was associated with improved socio-emotional adjustment, AI literacy, and perceived AI support among vocational students. A non-equivalent pretest-posttest control-group design was implemented with 168 Grade 10–11 students from four intact classes in two public vocational schools in Way Kanan, Indonesia. The AI-supported condition (n = 84) received activities integrating AI literacy, reflective prompting, feedback evaluation, peer dialogue, and teacher-mediated socio-emotional reflection, while the comparison condition (n = 84) received regular technology-enriched instruction. ANCOVA controlling for pretest scores showed higher adjusted posttest scores in the AI-supported condition for socio-emotional adjustment, F(1,165) = 18.72, p < .001, partial η² = .102; AI literacy, F(1,165) = 44.96, p < .001, partial η² = .214; and perceived AI support, F(1,165) = 16.84, p < .001, partial η² = .093. Findings suggest that structured, teacher-guided AI learning may support vocational students’ socio-emotional and AI-related development, although intact-class assignment and self-report outcomes require cautious interpretation.